Domiciliation of Triatoma pseudomaculata (Corrêa e Espínola 1964) in the Jequitinhonha Valley, State of Minas Gerais Domiciliação de Triatoma pseudomaculata (Corrêa e Espínola 1964) no Vale do Jequitinhonha, Estado de Minas Gerais - Girley Francisco Machado de Assis; Bernardino Vaz de Mello Azeredo; Ana Laura Carbajal de la Fuente; Liléia Diotaiuti; Marta de Lana (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
Impact of the vector control program was evaluated eight years after implantation of epidemiological surveillance for Chagas’ disease in Berilo, a municipality in the Jequitinhonha Valley of the Brazilian State of Minas Gerais. In all 5,242 domiciliary units (96% of the total) were inspected and 10 found to be infested by the triatomine bug Triatoma pseudomaculata. Triatomines were found associated with bats inside one house and in the peridomiciles of the other nine. None of the 111 Triatoma pseudomaculata captured was infected with Trypanosoma cruzi. Noireau et al16 traps were installed in (n=8) and around (n=100) the infested house but no Trypanpsoma cruzi-infected triatomines were found. None bat, opossums (Didelphis albiventris) and rat captured in the peridomicile were infected with Trypanosoma cruzi although 24% of the inhabitants of the house infested by Triatoma pseudomaculata were seropositive for the parasite, based on ELISA, IHA and IIF. Oito anos após a implantação da vigilância epidemiológica para doença de Chagas em Berilo, Vale do Jequitinhonha, MG, Brasil, foi realizada uma pesquisa para verificar o impacto do Programa de Controle Vetorial. Neste trabalho, 5. 242 (96%) unidades domiciliares foram vistoriadas. Dez estavam infestadas por Triatoma pseudomaculata. Em nove delas os insetos estavam infestando o peridomicílio e em uma casa foi constatado um foco intradomiciliar associado a morcegos. Foram capturados 111 insetos da espécie Triatoma pseudomaculata e nenhum exemplar estava infectado por Trypanosoma cruzi. Na casa infestada e em torno dela foram instaladas respectivamente 8 e 100 armadilhas de Noireau et al16 e nenhum triatomíneo foi capturado. Oitenta morcegos capturados e examinados também estavam negativos para Trypanosoma cruzi bem como três gambás (Didelphis albiventris) e um roedor, todos capturados no peridomicílio. Um porcentual de 24% dos moradores das casas infestadas por Triatoma pseudomaculata foi sororeativo (ELISA, HAI e IFI) para Tripanosoma cruzi.